Erratum to “The blink reflex and its modulation – Part 1: Physiological mechanisms” [Clin. Neurophysiol. 160 (2024) 130–152, (S1388245723007915), (10.1016/j.clinph.2023.11.015)] - Kofler, Markus; Hallett, Mark; Iannetti, Gian Domenico; Versace, Viviana; Ellrich, Jens; Téllez, Maria J.; Valls-Solé, Josep (Clinical Neurophysiology, 2024)
The Publisher would like to inform you that unfortunately a cross-reference contained within this article was not updated in proof. The Publisher apologises for this error and provides the corrected reference below. Gunduz A, Valls-Solé J, Serranová T, Coppola G, Kofler M, Jääskeläinen SK. The blink reflex and its modulation – Part 2: Pathophysiology and clinical utility. Clin Neurophysiol 2024; 160: 75-94.
CRIS-Team Scopus Importer:2024-04-19